2018
DOI: 10.5194/bg-2018-280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mechanistic model for electrical conduction in soil–root continuum: a virtual rhizotron study

Abstract: 19Electrical Resistivity Tomography (ERT) has become an important tool to study soil water fluxes processes. We see a greater anisotropy in a sandy medium when compared to a loamy medium. 33We find that the water uptake process dominates the bulk electrical properties. The Gauss-Newton 34 type ERT inversion of virtual rhizotron data demonstrate that, when root-soil electrical 35 conductivity contrasts are high, it can lead to error in water content estimates since the electrical 36 conductivity is partly due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Similarly, Anderson and Higinbotham (1976) found that σ cr of maize cortical sleeves was comparable to the stele σ cl . Recently, Rao et al (2018) found that maize root conductivity decreases as the root cross-sectional area increases, and that primary roots were more conductive than brace roots. By contrast, BIA studies on woody plants have supported the hypothesis of a radial isolation effect of bark and/or suberized tissues (Čermák et al 2006;Aubrecht et al 2006).…”
Section: Current Pathways In Rootsmentioning
confidence: 99%
“…Similarly, Anderson and Higinbotham (1976) found that σ cr of maize cortical sleeves was comparable to the stele σ cl . Recently, Rao et al (2018) found that maize root conductivity decreases as the root cross-sectional area increases, and that primary roots were more conductive than brace roots. By contrast, BIA studies on woody plants have supported the hypothesis of a radial isolation effect of bark and/or suberized tissues (Čermák et al 2006;Aubrecht et al 2006).…”
Section: Current Pathways In Rootsmentioning
confidence: 99%
“…In most soil types, electrical resistivity (ER) can be described as a function of porosity, saturation of electrolyte, its pH and mineralization within the pores (Archie, 1942), clay con-tent (and generalized Archie's laws) and temperature (e.g., Campbell et al, 1949). Water content could be derived from the measured ER using pedotransfer functions such as the well-known Archie's law or other approaches (e.g., Rhoades et al, 1976;Waxman and Smits, 1968). Since absolute soil moisture content is of limited interest for researchers and professionals which are focused on the soil water availability for the plant, several studies relate the application of the variation of ERT or the fraction of electrical resistivity variation (FERV) introduced by Brillante et al (2016) as a predictor of the fraction of transpirable soil water (FTSW) and related variables.…”
Section: Noninvasive Measurements and Electricalmentioning
confidence: 99%
“…In this study we made considerations to create a more natural environment for plant growth. Recent studies [28, 38] employ 2D rhizotrons that allow the direct observation of the RSA. The advantage of such systems is that the quantitative ability of EIT could be further explored by scanning root length with other computed-tomography methods.…”
Section: Discussionmentioning
confidence: 99%
“…This field is still under continuous development, and new approaches are being established. For instance, Rao et al [38] suggest a combined use of ERT and plant-water-flow models to further understand their pedophysical interactions with soil.…”
Section: Introductionmentioning
confidence: 99%